ENERGY SECURITY AND EFFICIENCY – POLAND’S POWER SECTOR CASE - Hebda, Wiktor (Serbian political thought, 2025)
Ensuring a nation’s energy security is crucial to its overall functioning. The current geopolitical realities have clearly undermined the energy stability of many European countries, including Poland. Moreover, the complicated international situation has made the process of modernization and energy transformation difficult. Poland has been implementing decarbonization for many years, which involves the gradual abandonment of hydrocarbons in favor of low- and zero-emission energy sources. One of the initiatives strengthening energy security is also increasing the efficiency of the power sector. In this case, not only the modernization and reconstruction of the electricity generation structure, but also the transmission grids are necessary. Reducing the energy intensity of the economy remains an important priority of the energy policy not only for Poland but also for every developing country. This paper aims to explore the Polish electricity sector in relation to its significance for national security and the urgent requirement to boost energy efficiency in the years ahead. The findings suggest that establishing new energy sectors is essential; without dynamizing modernization and decarbonization of the power sector, achieving a stable and efficient energy system will be difficult to achieve.